Exponential Dichotomy and Mean Square Bounded Solutions of Linear Stochastic Ito Systems - Stanzhitskyi, O.M. (Нелінійні коливання, 2001)
We prove that a sufficient condition for stochastic Ito systems to be exponentially dichotomous
on the semiaxis is that the nonhomogeneous system havemean square bounden solutions.